CSI, crime scene investigation. The complete fourth season [videorecording (DVD)] - Zuiker, Anthony E., 1968- (CBS DVD., 2004)
In the city of Las Vegas, Nevada, with its constant influx of visitors, criminals are provided with ripe targets of all varieties. Luckily for the victims, the Las Vegas Police Department's night shift Crime Scene Investigations unit is led by Gil Grissom. With almost obsessive dedication towards his quest for the facts, he and his elite team of criminalists work various perplexing cases using scientific skills and equipment that are capable of finding valuable clues from the most seemingly unlikely sources.